ڈاکٹر اسلم فرخی کی خاکہ نگاری - Muhammad Azhar Malik; Shakeel Hussain; Dr. Hammad Rasool (Khayaban - خیابان, 2022)
In Urdu literature, Dr. Aslam Farkhi is a unique writer due to his creative aspects. As a sketcher, he wrote down the culture and values associated with the personalities he wrote about. All these personalities feel like history and civilization. They were part of not only highlighting the strengths of the characters but also describing the weaknesses in such a way that those weaknesses feel part of their mood. These sketches by Aslam Farkhi are a valuable addition to Urdu literature, enabling the reader to access the literary history associated with these figures.